Testing Rational Expectations in Vector Autoregressive Models - Søren Johansen; Anders Rygh Swensen (Statistics Norway, Research Department, 1994)
Assuming that the solutions of a set of restrictions on the rational expectations of future values can be represented as a vector autoregressive model, we study the implied restrictions on the coefficients. Nonstationary behavior of the variables is allowed, and the restrictions on the cointegration relationships are spelled out. In some interesting special cases it is shown that the likelihood ratio statistic can easily be computed.
Keywords: C32; 330; VAR-models; cointegration; rational expectations.